Effect of root canal filling materials on dimensions of cone-beam computed tomography images - Daniel Almeida Decurcio; Mike Reis Bueno; Ana Helena Gonçalves de Alencar; Olavo César Lyra Porto; Bruno Correa Azevedo; Carlos Estrela (University of São Paulo, 2012)
OBJECTIVE:To evaluate the discrepancy of root canal filling (RCF) measurements obtained from original root specimens and cone-beam computed tomography (CBCT) images. MATERIAL AND METHODS: Seventy-two human maxillary anterior teeth were prepared up to an ISO #50 K-File 1 mm short of the apical foramen. Thus, the teeth were randomly divided into 8 groups, according to the root canal filling material: Sealapex ®, Sealapex®+gutta-percha points, Sealer 26®, Sealer 26®+gutta-percha points, AH PlusTM, AH PlusTM+gutta-percha points, Grossman Sealer, and Grossman Sealer+gutta-percha points. After root canal preparation and RCF, CBCT scans were acquired and the specimens were sectioned in axial, sagittal and coronal planes. The RCF measurements were obtained in different planes and thicknesses to determine the discrepancy between the original root specimens (using a digital caliper) and the CBCT images (using the scanner's proprietary software). One-way analysis of variance and Tukey tests were used for statistical analyses. The significance level was set at α=5%. RESULTS: Measurements of the different endodontic filling materials were 9% to 100% greater on the CBCT images than on the original root specimens. Greater RCF dimensions were found when only sealers were used, with statistically significant difference among the groups. CONCLUSIONS: RCF dimensions were greater on CBCT images than on the original root specimens, especially when only sealer was used.